Cohesion in Qur'ānic narrative: a study of monologue and dialogue patterns in sūrat al-Kahf (chapter of the cave) - Maisa Yahya Mahmoud Abu-Athreh,; Ashinida Aladdin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Cohesion is the use of grammatical and lexical ties to connect text segments. While cohesion in Qur’ānic discourse has received scholarly attention, the mechanisms by which it operates in narratives that shift between monologue and dialogue remain understudied. This gap limits our understanding of how the Qur’ān maintains narrative unity and rhetorical coherence across complex discourse structures. This study aims to fill this gap by identifying and analyzing grammatical cohesive devices in the story of the Companions of the Cave in Sūrat al-Kahf, applying Halliday and Hasan’s (1976) model to uncover how cohesion supports narrative unity and rhetorical function. The study applies both qualitative and quantitative analyses, examining the frequency, function, and distribution of cohesive devices in relation to monologue and dialogue structures. The findings reveal that grammatical cohesion is primarily achieved through references and conjunctions, which establish semantic connections between ayahs (verses).The monologue pattern exhibits a higher density of referential cohesion, while dialogue pattern relies more on conjunctions to achieve textual flow. The study identifies two levels of referential cohesion: micro level cohesion, where uncommon referents contribute to coherence within individual ayahs, and macro-level cohesion, where branched referents extend coherence across larger segments in the story. Additionally, the study highlights the interplay of multiple and interchangeable referents, particularly personal and demonstrative pronouns, which facilitate smooth transitions between monologue and dialogue sections. The additive conjunction (wa/and) plays a crucial role in maintaining discourse flow and textual continuity. These findings contribute to linguistic and Qur’ānic studies, providing insights into the stylistic and structural uniqueness of Qur’ānic narrative techniques.